2007
DOI: 10.1161/atvbaha.107.142109
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Glutathione Reductase in Macrophages Decreases Atherosclerotic Lesion Formation in Low-Density Lipoprotein Receptor–Deficient Mice

Abstract: Objective-Thiol oxidative stress leads to macrophage dysfunction and cell injury, and has been implicated in the development of atherosclerotic lesions. We investigated if strengthening the glutathione-dependent antioxidant system in macrophages by overexpressing glutathione reductase (GR) decreases the severity of atherosclerosis. Methods and Results-Bone marrow cells infected with retroviral vectors expressing either enhanced green fluorescent protein (EGFP) or an EGFP-fusion protein of cytosolic GR (GR cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Two weeks before irradiation and bone marrow transplantation, recipient LDLR −/− mice were put on acidified water containing sulfamethoxazole (160 ng/mL) and trimethoprim (32 ng/mL) and were maintained on antibiotics for 4 wk. Bone marrow cells were isolated by flushing the femurs and tibias with Iscove's Modified Dulbecco's Medium (Gibco) containing 2% (vol/vol) FBS as described previously (43). Bone marrow cells (2 × 10 6 cells in 0.2 mL) were injected via the lateral tail vein into lethally irradiated (two equal doses of 4.7 Gy, 3 h apart; Mark I-68 Irradiator; JL Shepherd) recipient mice (n = 5 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks before irradiation and bone marrow transplantation, recipient LDLR −/− mice were put on acidified water containing sulfamethoxazole (160 ng/mL) and trimethoprim (32 ng/mL) and were maintained on antibiotics for 4 wk. Bone marrow cells were isolated by flushing the femurs and tibias with Iscove's Modified Dulbecco's Medium (Gibco) containing 2% (vol/vol) FBS as described previously (43). Bone marrow cells (2 × 10 6 cells in 0.2 mL) were injected via the lateral tail vein into lethally irradiated (two equal doses of 4.7 Gy, 3 h apart; Mark I-68 Irradiator; JL Shepherd) recipient mice (n = 5 per group).…”
Section: Methodsmentioning
confidence: 99%
“…A role of GR in cardiovascular disease (CVD) also has been investigated (104,149,196) but specific nuclear functions have not been delineated. Decreased levels of GSH and GSHrelated antioxidant enzymes, GR, GST, GPx, have been observed in human atherosclerotic lesions.…”
mentioning
confidence: 99%
“…Decreased levels of GSH and GSHrelated antioxidant enzymes, GR, GST, GPx, have been observed in human atherosclerotic lesions. Conversely, overexpression of GR targeted to cytoplasm or mitochondria in bone marrow-derived cells protected cells from oxidized LDL-induced mitochondrial hyperpolarization and reduced atherosclerotic lesion formation (149). Studies to define the role of GR in CVD have been extended to the regulation of signaling pathways.…”
mentioning
confidence: 99%
“…These data raise the question whether protein S-glutathionylation is limited to only select proteins and specific pathways or whether this unique post-translational modification may play a broader functional role in monocytes and macrophages. In support of the latter hypothesis, we found that metabolic stress increases global S-glutathionylation in peritoneal macrophages from mice fed a high-fat diet (HFD) (47). Increased S-glutathionylation correlated with functional changes in these macrophages, including the hypersensitization to chemokine-induced adhesion and accelerated monocyte chemotaxis, a phenomenon we termed metabolic priming of monocytes (47,62).…”
mentioning
confidence: 63%
“…To overexpress human Grx1 in THP-1 monocytes, we used a doxycycline-inducible Tet-On adenoviral system expressing a Grx1-EGFP fusion protein (47,62). THP-1 monocytes were incubated for 24 h with adenoviruses (multiplicity of infection = 25) in complete growth media.…”
Section: Overexpression Of Grx1 and Catalasementioning
confidence: 99%